The Contributions of Competitions to Cities and Urban Design: n Merzifon Municipality’s Business and Life Center Architectural Project Competition - Baris Ergen (Universitas Islam Negeri Sunan Ampel Surabaya, 2021)
Competitions are a significant means of focusing on specific spaces in cities and forming public opinion. Competitions result in many professionals such as architectures, urban planners, urban designers, landscape architects, civil engineers, etc. proposing lots of designs for the same space, and thereby submitting various solution offers for it. Therefore, competitions are important not only for their results, but also for increasing knowledge about the occupational groups of design and the shaping of urban open spaces and built environments, in other words, cities. This study analyzes competitions’ contributions to urban design based on the experience of Merzifon Municipality’s Business and Life Center Architectural Project Competition. The discipline of urban design, which plays an important role in forming the urban open spaces and built environments, is enriched by competitions. The approaches developed in the projects that compete for the urban spaces focused on the competitions play an important role in shaping cities.